2024
DOI: 10.3390/jof10030164
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Interaction between Oil Palm and Phytophthora palmivora in Bud Rot Disease: Insights from Transcriptomic Analysis and Network Modelling

Mariandrea García-Gaona,
David Botero-Rozo,
Leonardo Araque
et al.

Abstract: Bud Rot, caused by Phytophthora palmivora, is considered one of the main diseases affecting African oil palm (Elaeis guineensis). In this study, we investigated the in vitro molecular dynamics of the pathogen–host interaction by analyzing gene expression profiles from oil palm genotypes that were either susceptible or resistant to the disease. We observed distinct interactions of P. palmivora with resistant and susceptible oil palms through co-expression network analysis. When interacting with susceptible geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
1
3
0
Order By: Relevance
“…Our result showed that genes related to the uptake of nutrients are co-expressed with candidate effectors and have similar pattern expressions as those previously reported when P. palmivora (CPPhZC_05) infected oil palm [22]. Specifically, we evaluated two genes that encode apoplastic effectors (Gh17 and CXE), which contained hydrolytic domains.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Our result showed that genes related to the uptake of nutrients are co-expressed with candidate effectors and have similar pattern expressions as those previously reported when P. palmivora (CPPhZC_05) infected oil palm [22]. Specifically, we evaluated two genes that encode apoplastic effectors (Gh17 and CXE), which contained hydrolytic domains.…”
Section: Discussionsupporting
confidence: 78%
“…To study differences in isolates, we used a qRT-PCR approach to quantify ten previously detected P. palmivora genes involved in oil palm infection [22]. Hallmarks of the infection, Hmp1 and NmrA, were expressed during compatible infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations